Pigmented paravenous retinochoroidal atrophy -: A literature review supported by seven cases - Kükner, AS; Yilmaz, T; Çelebi, S; Aydemir, O; Ulas, F (Karger, 2003)
Seven patients (4 men and 3 women, ranging in age from 27 to 64 years) with pigmented paravenous retinochoroidal atrophy, a rare disorder of unknown origin, were studied. The mean follow-up time was 18.5 months. Fundus examinations were performed, and color fundus photographs were taken. In addition to fluorescein angiography, visual field examinations, color vision and electroretinographic tests were performed. All 7 patients were asymptomatic, with visual acuities ranging from 3/10 to 10/10. Both fundi showed patches of retinochoroidal atrophy and pigmentation along the retinal veins in all patients. Fluorescein angiography showed hyperfluorescence due to the pigment epithelial atrophy together with hypofluorescence corresponding to bone spicule pigment clumping. Visual field tests showed scotomas corresponding with areas of atrophy along the retinal veins. The electroretinography showed reduced responses in 2 cases. Color vision was normal in all cases. The patients had no history of trauma or a previous inflammatory process. Serology for syphilis, Toxoplasma and cytomegalovirus as well as a skin test for tuberculosis were negative. When the patients were seen at the end of the follow-up period, no variation of the findings was noted. Although the fundus abnormalities can be mild or severe, retinal function tests indicated that this is a geographic and not a generalized disorder. Copyright (C) 2003 S. Karger AG, Basel.
Keywords: pigmentation; paravenous distribution; retinochoroidal atrophy